Bone marrow uptake during parathyroid scintigraphy is a consequence of extremely high parathyroid hormone levels - Koc, Z.; Balci, T. (Springer, 2012)
[Abstract Not Available]
25th Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- OCT 27-31, 2012 -- Milan, ITALY
Keywords: parathyroid scintigraphy; Tc-99m MIBI; PTH; bone marrow